'The West' and 'the rest' in international interventions: Eurocentrism and the competition for order. Issue 3 (4th May 2019) - Turner, Mandy; Kühn, Florian P.
ABSTRACT: This special issue was provoked by the desire to critically interrogate the frequently made Eurocentric assertions by many politicians and academics that 'the West' and 'the rest' are fundamentally different in terms of their aims and methods of intervention. Bringing together scholars of intervention with regional experts on China, Russia, the Gulf Arab states and Turkey, detailed empirical knowledge is used to analyse current interventionist practices by Western and non-Western actors, and to assess whether they are similar or fundamentally different. Through their analyses of different forms of intervention (that constitute a wider range of actions than just 'boots on the ground'), the authors present informed critiques of existing categories, question the episteme of interveners, and observe changes of language in the justifications made for interventions – for both Western and non-Western actors. These allow us to conclude overall that the difference between 'the West' and 'the rest' in interventionist terms is not so huge, and that existing categories and frameworks in intervention studies are inadequate and require a rethink.